KARAKTERISASI FAKTOR PENENTU KEBERLANJUTAN PENGEMBANGAN AYAM KUB DI KABUPATEN GARUT - Prawiranegara, Darojat; Mulijanti, Siti Lia (Badan Penelitian dan Pengembangan Daerah Provinsi Jawa Barat, 2020)
Inventory of factors determining the continuation of keeping KUB chickens by poor villager households, disseminated under #Bekerja program in 4 sub districts of Garut regency, was carried out through a survey study in September to November 2018. The data sampling was conducted purposely, consisting of representatives of various sources related to the development of keeping the KUB chickens gathered in FGD (Focus Group Discussion). The data consisted of primary data and secondary data. The data were analysed descriptively and by using multiple regression which was performed using SPSS 16. The results showed that internal factors consisted of quality of direct management by poor villager households, the existence of suppliers, market intermediaries, consumers and competitors. Whilst the external factors were the guidance of government services officers, the product selling price and the distance of location of the market. Furthermore the results showed that the motivation of RTM, supplier of business inputs, marketing intermediaries, consumer desires, officer guidance, selling prices, business location and quality of KUB chickens significantly influence the development of KUB chickens. Whilst competitor and promotion did not significantly influence the development of keeping KUB chickens.